Determination of sexual dimorphism in humans by measurements of mandible on digital panoramic radiograph - V Sairam; M V Geethamalika; Praveen B Kumar; G Naresh; Gareema P Raju (Contemporary Clinical Dentistry, 2016)
Background: Identification of sex is the first step in forensic science obtained from skeletal remains. Mandible, being a strong bone that is difficult to damage and disintegrate, is an important tool in sex determination. The present study is aimed to assess, compare, and evaluate the mandibular measurements as seen on digital panoramic radiographs to analyze their use in sexual dimorphism assessment. Materials and Methods: This retrospective study was conducted using digital panoramic images of 100 each in both genders. Mandibular measurements were carried out utilizing RadiAnt DICOM Viewer 2.2.9 (32 bit) software (Medixant Company, Poland) and subjected to statistical analysis. Results: Descriptive statistics for all the parameters on the right and left sides of mandible in both males and females were analyzed. Inferential statistics were performed using t-test to compare males and females with different variables. A statistical significance of P< 0.001 has been demonstrated for all the variables (except linear measurement of mandibular foramen). All variables showed increased measurements in males than in females. The accuracy of sex determination in mandibular ramus measurements is 79.5% on right side and 77% on left side, where as, in linear mandibular measurements it is 76% on right side and 79.5% on left side. Conclusion: Mandibular measurements on digital radiograph are useful in sex determination, and this study can be compared with other similar studies.